СУЧАСНІ ПРОБЛЕМИ ФУНКЦІОНУВАННЯ ТЕЦ УКРАЇНИ - Басок, Б.І.; Дубовський, С.В.; Куделя, П.П. (Інститут електродинаміки НАН України, Київ, 2022)
A brief analysis of the state, problems and external conditions of operation of combined heat and power plants in Ukraine, as well as their changes during hostilities. Issues and proposals for the choice of rational modes of operation of CHP in the conditions of primary fuel shortage, reduction of electrical loads of the energy system, the risk of possible damage to energy equipment during hostilities and in the postwar recovery. It is proposed to develop and implement in the practice of planning the development of survivability criteria of stations with connected district heating systems. References 7, figures 4.